2013
DOI: 10.1007/s00436-013-3360-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of Theileria equi in horses and their association with possible tick vectors in the state of Rio de Janeiro, Brazil

Abstract: The aim of this study was to detect Theileria equi (Laveran 1901) DNA in horses and ticks using real-time PCR and to list the factors associated with infection in animals located in the Seropedica and Petropolis municipalities of the state of Rio de Janeiro. We tested blood samples from 314 horses and samples from 300 ticks, including 191 Amblyomma cajennense, 104 Dermacentor nitens, and 5 Ixodida larvae. Factors inherent to the horse, the ownership, and animal management were obtained from an epidemiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 30 publications
3
33
0
Order By: Relevance
“…Regarding various farm practices under study, due to the breech in management practices in the unorganized farm (Table 3), the incidence of direct contact with tick vectors increases resulting in significant amplification of infection (Kouam et al 2010;Moretti et al 2010;Abutarbush et al 2012;Steinmana et al, 2012;Peckle et al 2013;Sumbria et al 2015). Similar significant result was noted by serological testing also (Table 4).…”
Section: Discussionsupporting
confidence: 81%
“…Regarding various farm practices under study, due to the breech in management practices in the unorganized farm (Table 3), the incidence of direct contact with tick vectors increases resulting in significant amplification of infection (Kouam et al 2010;Moretti et al 2010;Abutarbush et al 2012;Steinmana et al, 2012;Peckle et al 2013;Sumbria et al 2015). Similar significant result was noted by serological testing also (Table 4).…”
Section: Discussionsupporting
confidence: 81%
“…These results shows that T. equi is widespread in the region studied, suggesting high levels of transmission. Additionally, our data is in accordance with previous studies which have demonstrated that the disease is endemic in Brazil (CUNHA et al, 1996;BALDANI et al, 2004;HEIM et al, 2007;SANTOS et al, 2011;PECKLE et al, 2013). To our knowledge, this is the first report of the detection of IgG antibodies anti-T. equi in Paraná state.…”
supporting
confidence: 82%
“…It should be mentioned that the municipality of Guarapuava, which is located in the high-altitude region of the state of Paraná, has a humid semitropical climate, with an annual average temperature of approximately 16 °C, with winter temperatures that reach bellow 0 °C. Peckle et al (2013) also reported lower infection frequency of T. equi in horses of Petrópolis, a region of Rio de Janeiro state with high altitude, where the annual average temperature is 16 °C and winter temperatures of 0 °C.…”
mentioning
confidence: 99%
“…Therefore, sensitive and specific tests for Equine Piroplasmosis diagnosis are required to prevent introduction of causative agents into countries that are regarded free of the infection or disease (Mahmoud et al 2016).The results presented here indicate that PCR is a sensitive assay and proves that the causative agents of Equine Piroplasmosis are circulating in the studied area. Studies performed in Brazil using PCR or IFAT have also detected both agents in horses, as the one reported in Minas Gerais (Heim et al 2007), Rio Grande do Sul (Torres et al 2012), Rio de Janeiro (Peckle et al 2013) and São Paulo (Dória et al 2016). Antibodies against Anaplasma phagocytophilum were detected in low levels however all blood and tick samples were negative by PCR.…”
Section: Discussionmentioning
confidence: 94%
“…The diagnoses of Equine Piroplasmosis can be done by direct and indirect methods; however, molecular assays appears as useful tools to identify the infection (Figueroa et al 1993, Bashiruddin et al 1999, Nicolaiewsky et al 2001, Peckle et al 2013, Malekifard et al 2014, Dória et al 2016, Mahmoud et al 2016. Therefore, sensitive and specific tests for Equine Piroplasmosis diagnosis are required to prevent introduction of causative agents into countries that are regarded free of the infection or disease (Mahmoud et al 2016).The results presented here indicate that PCR is a sensitive assay and proves that the causative agents of Equine Piroplasmosis are circulating in the studied area.…”
Section: Discussionmentioning
confidence: 99%